THE TRANSLATION SHIFTS AND TRANSLATION PROCEDURES OCCURRED IN GARUDA INDONESIA’S MAGAZINE: COLOURS - I Wayan Budiarta; Kasni Ni Wayan; Anak Agung Istri Manik Warmadewi (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This study aimed at identifying and analyzing the types of translation shifts and translation procedures in the Garuda Indonesia: Colors magazine and its translations. The theory used was the theory of translation shift by Catford (1965) and the theory of translation procedures The results showed that in the Colors: Quiet Seoul magazine article, two categories of shifts were come across. Meanwhile, in the Colors: Explore Banyuwangi magazine article there were only Category Shifts found, namely structure shift, class shift, unit shift and intra-system shift. In terms of translation procedures, this research indicated that in the Colors: Quiet Seoul magazine article, there were two translation procedures detected, namely: Adaptation and Borrowing. Meanwhile, in the Colors: Explore Banyuwangi magazine article (pp. 96-104), there were 11 translation procedures found, namely: Adaptation, Amplification, Borrowing, Calque, Compensation, Generalization, Literal Translation, Modulation, Particularization, Reduction, and Transposition.